An optimization model for water quantity and quality integrated management of an urban lake in a water deficient city. Issue 9 (21st October 2017) - Zheng, Jian-Feng; Jiao, Ji-Dong; Zhang, Shuo; Sun, Li-Ping
Abstract: This paper presents an optimization model for water quantity and quality integrated management of an urban lake in a water deficient city. A representative water quantity and quality safeguard system served urban lake, including multi-source water supply facilities, recirculating water purification facilities and surplus water discharge facilities, is widely used in Chinese water deficient cities. Because it is complicated, any mismanagement will result in water quality deterioration, water waste and high operation cost. The presented model attempts to achieve the objectives of controlling water pollution, reducing economic cost and improving water utilization efficiency through an optimized operating water safeguard system. The model is applied to Qingjing Lake in Tianjin, China. Results show that the model plays a more positive role for water quantity and quality integrated management.